Characterizing herbivore resistance mechanisms: spittlebugs on brachiaria spp. as an example - Parsa, S; Sotelo, G.; Cardona, C. (MyJove Corporation, 2011)
Plants can resist herbivore damage through three broad mechanisms: antixenosis, antibiosis and tolerance. Antixenosis is the degree to which the plant is avoided when the herbivore is able to select other plants. Antibiosis is the degree to which the plant affects the fitness of the herbivore feeding on it.Tolerance is the degree to which the plant can withstand or repair damage caused by the herbivore, without compromising the herbivore's growth and reproduction. The durability of herbivore resistance in an agricultural setting depends to a great extent on the resistance mechanism favored during crop breeding efforts.